2011
DOI: 10.1161/strokeaha.110.600064
|View full text |Cite
|
Sign up to set email alerts
|

Is Investigating for Carotid Artery Disease Warranted in Non-Cortical Lacunar Infarction?

Abstract: Abstract-Carotid intervention in severe carotid stenosis after an anterior circulation ischemic event reduces the risk of further infarcts if the surgery is performed soon after the incident event. At present, there is no recommendation to differentiate among subtypes of anterior circulation infarcts or transient ischemic events. However, evidence is mounting that demonstrates a difference in pathophysiology of lacunar and nonlacunar (large artery) infarcts. The natural history of lacunar strokes is different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The pathogenesis of cerebral WMLs and the chain of events causing clinical infarctions are multifactorial and remain incompletely elucidated (26,28). However, ischemic injury to the white matter presumably plays an important role in the development of WMLs.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of cerebral WMLs and the chain of events causing clinical infarctions are multifactorial and remain incompletely elucidated (26,28). However, ischemic injury to the white matter presumably plays an important role in the development of WMLs.…”
Section: Discussionmentioning
confidence: 99%
“…Stenosis of extracranial carotid arteries is usually incidental even in the presence of lacunar strokes but atherosclerosis of smaller cerebral arteries is a predominant identifiable cause of lacunar stroke. [4,5] As the largest intracranial artery, middle cerebral artery (MCA) is the most frequently involved in stroke and transient ischemic attacks. MCA stenosis appears to occur with lacunar striato-capsular infarcts due to occlusion of small perforating arteries by atheroemboli.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that lacunar mechanism is different from the usual stroke mechanism and these infarcts may need a different approach to therapy and prevention (5). More recently, it has been controversially suggested that lacunar strokes neither warrant investigation for carotid stenosis (6) nor benefit from thrombolysis with recombinant tissue plasminogen activator (rTPA) (7, 8). It is possible that these proposals may have arisen as result of confusion between infarcts with “lacunar” phenotype and those with lacunar mechanism (9).…”
Section: Introductionmentioning
confidence: 99%